A case report of Andersen-Tawil syndrome misdiagnosed with myodystrophy - Zhao, Xiuqin; Zu, Hengbing; Yao, Kai (Frontiers in Neurology, 2023)
Andersen-Tawil syndrome (ATS) is a rare periodic paralysis caused by the KCNJ2 gene mutation. Here, we report on an ATS patient misdiagnosed with myodystrophy. A 66-year-old man presented with a 60-year history of episodic weakness in the proximal muscles of the upper and lower limbs. The man has been diagnosed with muscle pathology and has undergone genetic examinations in many hospitals since childhood. We conducted a correct diagnosis in combination with the patient’s history, electrical physiology, and genetic analysis and identified a heterozygous KCNJ2 gene variant (c.220A > G; p.T74A). Patients with ATS can develop permanent myasthenia characterized by chronic progressive myopathy. ATS patients should also pay special attention to the risks of anesthesia in surgery, including malignant hyperthermia (MH), muscle spasms affecting tracheal intubation or ventilation, and ventilator weakness. Early diagnosis and therapy could help delay the onset of myasthenia and prevent risks associated with anesthesia accidents.